Optimasi Komposisi Makanan untuk Penderita Hipertensi Menggunakan Algoritma Genetika dan Simulated Annealing - Agustin Kartikasari; Dian Eka Ratnawati; Titis Sari Kusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Hypertension ranks third largest as a disease that causes early death (Depkes, 2006). One way to prevent and treat hypertension is to modify food intake. But for the layman, arranging the composition of everyday food is still considered difficult. The problem is then solved by a combination of genetic algorithm and simulated annealing. The combination of these two algorithms aims to improve the solutions generated by genetic algorithms and avoid the occurrence of early convergence. At this problem solving used one-cut crossover method, reciprocal exchange mutation, elitism selection, and neighborhood move on simulated annealing. Based on the parameters test, the best parameter values ​​are population size of 1000, the number of generations is 200, the combination value of cr and mr is 0.6 and 0.4, the final temperature (Tn) is 0.2, and the cooling rate of 0.9. While based on system testing conducted can be seen that the combination of both algorithms able to solve this problem because the resulting nutritional content is within the limit of tolerance given by nutritionists is ± 10%